Pengaruh Pembelajaran Tatap Muka Terhadap Psikologis Siswa di Masa Pandemi COVID-19 - Anggraeni, Vidiya; Perdana, Parrisca Indra (Pendagogia: Jurnal Pendidikan Dasar, 2023)
Face-to-face learning during the COVID-19 pandemic certainly has its own challenges because they have to maintain each other's health protocols for teachers and students, as well as the importance of the students' own psychological condition. The purpose of this article is to obtain an overview and examine the effect of face-to-face learning on students' psychology during the COVID-19 pandemic. The research method used is a qualitative approach with data collection through interviews and in the form of a literature study. Analysis of the data used using content analysis, namely collecting, recording, managing data, and drawing conclusions to become scientific data. It is hoped that this limited face-to-face learning can have a positive impact on student psychology because, during the online learning process, students often feel stressed, lazy, and find it difficult to capture material during learning. The results of the research show that the face-to-face learning model provided by the educator is effective and has increased student learning; besides that, student psychology is getting better than before. This face-to-face learning is the best solution during the COVID-19 pandemic, as well as for the psychological condition of students.